Pola Asuh Orangtua dalam Mengantisipasi Dampak Penggunaan Gadget di Masa Pandemi Covid-19 - N. Najwa (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to determine how parents' upbringing on children's behavior in playing gadgets during the pandemic. This study uses a qualitative method with a phenomenological approach. From the results of the study, it can be concluded that the parenting style applied to children in playing gadgets generally uses democratic parenting. Parents' parenting behavior in responding to children who play with gadgets tends to use a gentle way, giving understanding to children about the negative effects of playing gadget and giving freedom to children to express themselves but still under strict supervision and control so that children use gadget for things the positive.